2018
DOI: 10.1111/dmcn.14080
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories and reference centiles for the impact of health conditions on daily activities of children with cerebral palsy

Abstract: Aim First, to describe the impact of health conditions on daily activities over time in children with cerebral palsy (CP) and to create age‐specific reference centiles. Second, to determine the amount of change typical over a 1‐year period, across Gross Motor Function Classification System (GMFCS) levels. Method A prospective, cohort design, with five assessments over 2 years, involved 708 children with a confirmed diagnosis of CP participating in the On Track Study (396 males, 312 females; mean age 6y [SD 2y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 24 publications
0
13
0
10
Order By: Relevance
“…In the 38 studies that investigated the activity component, the outcomes measured changes in mobility ( n = 17 studies), 16,17,31,35,39,46,49,51,53,54,58,60,65,72,76,78,83 walking, carrying, moving, and handling objects ( n = 11), 31,32,35,49,50,54,65,66,71,76,82 self‐care ( n = 11), 31,39,46,51,53,54,66,72,79–81 communication (verbal and non‐verbal) ( n = 7), 36,41,47,61–63,70 socializing ( n = 5), 36,39,41,48,53 regulating behavior within interactions ( n = 1), 39 looking after one's health (i.e. physical activity, well‐being) ( n = 5), 34,56,64,68,77 and managing diet and fitness ( n = 1) 34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 38 studies that investigated the activity component, the outcomes measured changes in mobility ( n = 17 studies), 16,17,31,35,39,46,49,51,53,54,58,60,65,72,76,78,83 walking, carrying, moving, and handling objects ( n = 11), 31,32,35,49,50,54,65,66,71,76,82 self‐care ( n = 11), 31,39,46,51,53,54,66,72,79–81 communication (verbal and non‐verbal) ( n = 7), 36,41,47,61–63,70 socializing ( n = 5), 36,39,41,48,53 regulating behavior within interactions ( n = 1), 39 looking after one's health (i.e. physical activity, well‐being) ( n = 5), 34,56,64,68,77 and managing diet and fitness ( n = 1) 34 .…”
Section: Resultsmentioning
confidence: 99%
“…32,38,43,57,59,69,82,84 The 38 studies retrieved on the activity component showed differences between levels of the GMFCS. The main outcomes investigated were mobility, 16,17,31,35,39,46,49,51,53,54,58,60,65,72,76,78,83 walking, carrying, moving, and handling objects, 31,32,35,49,50,54,65,66,71,76,82 selfcare, 31,39,46,51,53,54,66,72,[79][80][81] and communication. 36,41,47,[61]…”
Section: Discussionmentioning
confidence: 99%
“…How age may influence participation in family and recreational activities is complex and most likely depends on a multitude of child, family, and environmental factors (Alghamdi et al, 2017). Our accompanying study data on health conditions (Bartlett et al, 2018b) found that children, except for those in GMFCS level III, were likely to experience greater impact of health conditions on their daily life as they got older, and this was most prominent for children in GMFCS levels II and V. The impact of health conditions may be a plausible explanation for the possible decline found in frequency of participation for children in levels II and V.…”
Section: Discussionmentioning
confidence: 99%
“…Mother's ratings changed from 5 to 3 (Does part of the activity independently but needs help for some of the activity) for the following activities (items): drying body and wiping nose. In reviewing scores of other measures completed as part of a comprehensive assessment during the On Track Study, Naiwen's percentile change on the Early Clinical Assessment of Balance(McCoy et al, 2012) and the Child Health Conditions Questionnaire(Bartlett et al, 2018) indicate progress was 'less than expected'. Noteworthy, on the Child Health Conditions Questionnaire, mother reported pain was affecting Naiwen's daily activities a 'moderate extent' compared to the previous year when she reported a 'small extent'.…”
mentioning
confidence: 99%